STRATEGI ADAPTASI PENGRAJIN TENUN SIAK DI KABUPATEN SIAK - Nuri Maulana; Achmad Hidir (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research was in the Kabupaten Siak Provinsi Riau. The purpose of this study was to determine the profile of the life of craftsmen Weaving Tenun Siak in Kabupaten Siak. The research titled “Adaptation Strategies Craftsmen Tenun Siak in Kabupaten Siak”. Topics focus of this research is how adaptation strategies craftsmen Tenun Siak in Kabupaten Siak. This research subject craftsmen tenun siak in Kabupaten Siak and the leadership of the foundation that will be a source of information and research object. Samples were craftsmen tenun siak amounted to 9 workers who are in Kabupaten Siak and the leadership of the foundation. he author uses qualitative descriptive method and the data were analyzed qualitatively. Sampling was done by purposive sampling technique. Instruments of data are observation, questionnaires and documentation. The results showed that the workers tenun siak: a few strategies to meet the needs of households, namely: Biological Investment Strategies, Strategy successively , Educational Strategy, Investment Strategy Economics. Of all the craftsmen Tenun Siak, work as a weaver is the main worker but not a second job to help the family economy. Before becoming Weaving craftsmen Tenun Siak, all the craftsmen Tenun Siak training how to produce woven fabrics Tenun Siak follow organized by the government Dewan Kesenian Nasional Daerah (DEKRANASDA) Kabupaten Siak and partly trained work place . Keywords : Adaptation Strategies, Workers Tenun Siak .